An Introduction to Ælred's Chapter Discourses - Casey, Michael (Cistercian studies quarterly, 2010)
The article presents an introduction of a Cistercian customary discourses as interpreted by Ælred of Rievaulx, an English writer. It discusses the three main significant aspects of Saint Benedict's rules including to establish policy, to rule and to give orders. It mentions the implication of the deliverance of discourses which are done and delivered on a great liturgical feasts. It further offers passages depicting Ælred's interpretation of several liturgical discourses.